Ḍākṭar Puṭṭaparti abhinandana sañcika - Vēṇugōpālareḍḍi, Mallemāla; Hanumacchāstri, Jānamaddi, 1926-; Rāmappanāyuḍu, Nallapāṭi, 1934- (Abhinandana Samiti, 1977)
Souvenir comprising articles on the life and works of Puttaparti Narayanacharyulu, b. 1915, Telugu poet.